Peningkatan Hasil Belajar Siswa Tema IV Subtema III Menggunakan Model Portofolio Kelas V Sekolah Dasar - Ulfah Elkhaira Noor; Reinita Reinita; Zaiyasni Zaiyasni (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research was motivated by not maximizing student learning outcomes in integrated thematic learning in class V of SD Negeri 01 Belakang Campago Ipuh, Bukittinggi City. The purpose of this study is to describe an increase in learning outcomes in integrated thematic learning with a portfolio model in class V of SD Negeri 01 Belakang Campago Ipuh, Bukittinggi. The type of research is PTK using qualitative and quantitative approaches. Student learning outcomes in cycle I 72.5 increased to 92 in cycle II. Thus, integrated thematic learning by applying the Portfolio model can improve the learning outcomes of fifth grade students of SD Negeri 01 Campago Ipuh, Bukittinggi.Key Word : Result study, PKn, model Portofolio